Correction of refractive errors in patients with strabismus. Part I. Clinical problems associated with refraction, accommodation and convergence - Tokarz-Sawińska, Ewa (Klinika Oczna / Acta Ophthalmologica Polonica, 2012)
In Part I the problems associated with refraction, accommodation and convergence and their role in proper eye position/ visual alignment of the eyes as well as convergent, divergent and vertical alignment of the eyes have been described.